Drawing Phylogenetic Trees - Christian Bachmaier; Ulrik Brandes; Barbara Schlieper (ISAAC'05: Proceedings of the International Symposium on Algorithms and Computations, 2005)
We present linear-time algorithms for drawing phylogenetic trees in radial and circular representations. In radial drawings given edge lengths (representing evolutionary distances) are preserved, but labels (names of taxons represented in the leaves) need to be adjusted, whereas in circular drawings labels are perfectly spread out, but edge lengths adjusted. Our algorithms produce drawings that are unique solutions to reasonable criteria and assign to each subtree a wedge of its own. The linear running time is particularly interesting in the circular case, because our approach is a special case of Tutte's barycentric layout algorithm involving the solution of a system of linear equations.